Leiomiossarcoma de veia cava inferior - Crema,Eduardo (2008)
Leiomyosarcoma of the inferior vena cava is an extremely rare tumor, and it is reported to have a poor prognosis. The clinical findings are nonspecific and may precede the diagnosis by several years. Symptoms depend on the location and extension of the tumor. A complete surgical resection is the only proven therapeutic modality that prolongs the survival in patients with this lesion. We report a case of a 50 year-old patient with inferior vena cava leiomyosarcoma, who was submitted to a surgical treatment.